UNSUR KEBUDAYAAN DALAM NOVEL UNTU HIU KARYA ASTI PRADNYA RATRI (Kajian Antropologi Sastra) - Dewi, Endah Repsiana; Waluyo, Budi; Sulaksono, Djoko (Universitas Sebelas Maret, 2025)
A novel depicts the socio-cultural conditions of a society in the form of fiction and contains dramatic elements. One of the values contained in the novel is cultural value. Untu Hiu by Asti Pradnya Ratri is a Javanese novel that incorporates cultural elements. This study utilizes a qualitative descriptive method with a literary anthropology approach to examine the cultural elements contained within the novel Untu Hiu by Asti Pradnya Ratri. The data for this study consist of the analysis of documents, including words, phrases, clauses, and sentences found in the novel Untu Hiu by Asti Pradnya Ratri. The data collection for this study is conducted using document analysis with note-taking techniques. The results of this study indicate the presence of seven cultural elements in the novel Untu Hiu by Asti Pradnya Ratri, including: 1) language in the form of speech levels and dialects of Javanese; 2) knowledge system in the form of knowledge about the Javanese time calculation system; 3) social organization in the form of kinship systems, village government systems, and fishermen's social groups; 4) life equipment and technology systems in the form of cooking utensils, transportation tools, communication tools, and clothing; 5) livelihood system in the form of batik trade; 6) religious system in the form of belief in God, religious rituals, and myths; and 7) arts in the form of batik, carvings, songs, and wayang.